Anti-HIV tigliane diterpenoids from Reutealis trisperma. (June 2020) - Lu, Yan; Huang, Ya-Si; Chen, Chin-Ho; Akiyama, Toshiyuki; Morris-Natschke, Susan L.; Cheng, Yung-Yi; Chen, Ih-Sheng; Yang, Sheng-Zehn; Chen, Dao-Feng; Lee, Kuo-Hsiung
Abstract: Bioassay-guided fractionation of the n- butanol extract from the branches and leaves of Reutealis trisperma resulted in the isolation of six undescribed (crotignoids L ~ Q) together with two known (12-deoxyphorbol-13-hexadecanoate and 12-deoxyphorbol-13-myristate) tigliane diterpenoids. Their structures, especially the absolute configurations, were determined from extensive spectroscopic studies, including 2D NMR spectra, CD data analysis and electronic circular dichroism (ECD) calculations. All isolates were tested for anti-HIV activity against HL4-3 virus in MT4 cells. Except for crotignoid Q, the remaining seven tigliane diterpenoids exhibited potent anti-HIV activity with IC50 values ranging from 0.0023 to 4.03 μM. Graphical abstract: Image 1 Highlights: Six undescribed tigliane diterpenoids were obtained from Reutealis trisperma . Absolute configuration was determined by theoretical and experimental ECD spectra. Seven diterpenoids exhibited potent anti-HIV activity.